2016
DOI: 10.4049/jimmunol.1501558
|View full text |Cite
|
Sign up to set email alerts
|

The IL-12 Response of Primary Human Dendritic Cells and Monocytes to Toxoplasma gondii Is Stimulated by Phagocytosis of Live Parasites Rather Than Host Cell Invasion

Abstract: As a major natural host for Toxoplasma gondii, the mouse is widely used for the study of the immune response to this medically important protozoan parasite. However, murine innate recognition of toxoplasma depends on the interaction of parasite profilin with TLR11 and TLR12, two receptors that are functionally absent in humans. This raises the question of how human cells detect and respond to T. gondii. Here, we show that primary monocytes and dendritic cells from peripheral blood of healthy donors produce IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 53 publications
7
94
0
3
Order By: Relevance
“…In addition, primary monocytes are significantly more phagocytic than THP-1 cells, and in our experiments, ~30% of the intracellular T. gondii in primary monocytes are the result of phagocytosis events (data not shown). Indeed, phagocytosis of T. gondii by primary monocytes likely contributes to some of the IL-1β signal observed, as phagocytosis induces a stronger cytokine response than does invasion by the parasite (48). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, primary monocytes are significantly more phagocytic than THP-1 cells, and in our experiments, ~30% of the intracellular T. gondii in primary monocytes are the result of phagocytosis events (data not shown). Indeed, phagocytosis of T. gondii by primary monocytes likely contributes to some of the IL-1β signal observed, as phagocytosis induces a stronger cytokine response than does invasion by the parasite (48). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we observed that direct parasite-host cell contact is critical for TNF and IL-12 induction. 42 These findings are at odds with a recent study by Salazar Gonzalez et al , 43 who showed that T. gondii profilin stimulates human monocytes to secrete IL-6 and IL-12 in a TLR5-dependent manner. The basis of this discrepancy is unclear but may relate to the purity of the profilin or cell populations employed by the two laboratories.…”
Section: The Response Of Human Myeloid Cells To T Gondii Requires Phmentioning
confidence: 90%
“…42 Because of its major role in Th1 immunity, we decided to use IL-12 as the primary read-out in our subsequent experiments. The bioactivity of the IL-12 produced was confirmed in co-culture experiments in which stimulated monocytes as well as their supernatant were shown to trigger IFN-γ production from purified NK cells in an IL-12-dependent manner.…”
Section: The Human Innate Response To T Gondii: a Gaping Hole In Ourmentioning
confidence: 99%
See 2 more Smart Citations